Surfacing Alternatives for Unsealed Rural Roads - Henning, Theuns; Kadar, Peter; Bennett, Christopher R. (World Bank, Washington, DC, 2012)
Despite extensive road construction programs over the last century, a substantial proportion of roads remained unsealed especially in developing and emerging economies. As these economies develop, the demand arises to seal previously unsealed roads. The most economical transition point between unsealed and sealed roads depends on many conditions that need to be evaluated. The purpose of this Note is to provide guidance for decision makers, engineers and administrators on selecting the most appropriate surface for unsealed road given the prevailing conditions. It is based on the report "Surfacing Alternatives for Unsealed Roads" (report 37192).